RETRACTED ARTICLE: Examining the dynamics of pro-social rule-breaking among grassroots public servants - Naqib Ullah Khan; Peng Zhongyi; Wajid Alim; Heesup Han; Antonio Ariza-Montes (Humanities & Social Sciences Communications)
Abstract Understanding contemporary organizations hinges on the comprehension of rules and rule behavior. This scholarship explores the idea of employees rule-breaking for pro-social reasons. It challenges the belief that workplace rule violations are only motivated by personal gain and self-interest. Through two surveys conducted among grassroots civil servants working in public welfare programs, this research delves into the impact of social, relational, and bureaucratic factors on employees’ attitudes and behaviors toward pro-social rule-breaking. The study discovered that when individuals receive social support and witness co-workers’ rule-breaking, they are likelier to exhibit pro-social rule-breaking attitudes and behaviors. In contrast, organizational structure variables bureaucratic centralization and formalization and disciplinary control factors bureaucratic rule-breaking punishment and the certainty of detection diminish employees’ willingness to break the rules for pro-social reasons. The findings highlight the importance of recognizing social, relational, and bureaucratic organizational attributes to better understand pro-social rule-breaking among grassroots civil servants in public sector welfare agencies.